Australian Greens party members and supporters: their profiles and activities. Issue 2 (3rd March 2016) - Gauja, Anika; Jackson, Stewart
ABSTRACT: In an era of widespread party membership decline, there is debate over the utility, within the 'European' tradition, of conceptualising party membership as the locus of individual party engagement, and of maintaining membership and supportership as distinct categories in analysing party activism. This debate is particularly relevant to Green parties, which, through their particular social movement origins and emphasis on grass-roots democracy, bring into question the assumption that the activities and profile of members and supporters are functionally different. Using original data gathered from two surveys of Australian Greens party members and supporters undertaken in 2012 and 2013, the political activity, associational membership, ideological position, and demographic characteristics of these two groups are compared. While active party members are distinctive in their party-specific political activities and their ideological positioning, there is much less difference between the rest of the formal party membership and the party's active supporter base.